Co-designing accessible and inclusive patient information resources for gastrointestinal endoscopy using Patient and Public Involvement (PPI) and Universal Design for Learning (UDL) principles - Seán Fennessy; Liam Mulcahy; Brian O’Donnell; Hugh Mulcahy; Muirne Spooner; Edel McDermott (PLoS ONE, 2025)
Co-designing accessible and inclusive patient information resources for gastrointestinal endoscopy using Patient and Public Involvement (PPI) and Universal Design for Learning (UDL) Principles. Introduction Patients undergoing GI endoscopy can experience anxiety before their procedure, for numerous different reasons, including ineffective patient education resources received beforehand. Paper-based information leaflets are insufficient to accommodate for the diverse way in which people access, consume and process information. Public and patient involvement (PPI) and Universal Design for Learning (UDL) are two well-described pedagogical principles that strive to optimise patient-centred care and inclusivity. Objectives Our aim was to apply these principles to design more effective and accessible patient education materials, improving the health literacy of our patients. Working with patient partners, we identified the need to develop high-quality and trustable video resources for patients, that would be available on our hospital website. These videos were co-designed by patients and other key stakeholders. Results We used techniques such as storyboard development, the UDL educational principles of representation, engagement and expression, as well as the individual expertise of our stakeholder panel members to achieve appropriate and accessible information for our patient cohort. The development phase was an iterative process, with feedback and input from patient partners and other stakeholders playing a crucial role in prompting necessary adjustments for accuracy and patient understanding. Our project is the first guide in combining both PPI and UDL principles in the development of patient information and education materials. Conclusion By involving patients and other key stakeholders as partners, we improved the relevance and quality of our patient information content. Identification of patient partners and appropriate other stakeholders is an important initial step when co-designing patient information resources. The use of UDL in the co-design process allows for a structured approach to creating accessible content, highlighting important steps that otherwise may be overlooked by team members. Formal assessment of the impact of these co-designed videos, through quantitative and qualitative methods, will be assessed as part of a larger study.